The Pathway to Maturity: Processing of Ribosomal RNA in Saccharomyces cerevisiae - Raué, Hendrik A. (Cognizant Communication Corporation, 2018)

(untitled) (Gene Expr)
The 17-18S, 5.8S, and 25-28S rRNA species of eukaryotic cells are transcribed by RNA polymerase I into a single precursor molecule, from which external and internal spacer sequences are subsequently removed in an order series of nucleolytic reactions. Whereas the order of the cleavage reactions has long been established, only recently has significant progress been made in detailing the cis-acting elements and the trans-acting factors involved in this process. The use of recently developed systems for in vivo mutational analysis of yeast rDNA has greatly enhanced our knowledge of cis-acting structural features within the pre-rRNA, which are critical for correct and efficient removal of the spacer sequences. The same systems also allow a link to be forged between trans-acting processing factors and these cis-acting elements. In this review the newly obtained information will be summarized, focused predominantly on pre-rRNA processing in the yeast Saccharomyces cerevisiae.